Spectral Graph Theory: Eigen Values Laplacians and Graph Connectivity - J. Satish Kumar; B. Archana; K. Muralidharan, R. Srija (Metallurgical and Materials Engineering, 2025)
Spectral graph theory investigates how graph structures and specific matrix eigenvalues of adjacency matrices and Laplacian matrices relate to each other. The following paper explains fundamental spectral graph theory concepts by analyzing eigenvalues alongside Laplacians which help evaluate graph connectivity. The spectral characteristics of these matrices provide crucial insights into the graph structure that include properties regarding connectivity as well as expansion features and operational reliability. The paper explains essential theorems alongside applications and methodology of spectral analysis.